The Principle of Legality at the Crossroad: State Loss as a Requirement for Corruption Suspect Designation in Indonesia - Maulana, Aby (Kosmik Hukum, 2026)
The principle of legality (nullum crimen sine lege, nulla poena sine lege) stands as a foundational safeguard within contemporary criminal justice, ensuring legal certainty, predictability, and protection against arbitrary state action. In Indonesia, it is codified in Article 1(1) of the Penal Code (KUHP) and procedurally reinforced by the Criminal Procedure Code (KUHAP). Its doctrinal trajectory, however, shifted markedly after Constitutional Court Decision No. 25/PUU-XIV/2016, and Constitutional Court Decision No. 28/PUU-XXIV/2026 which annulled the phrase “may cause” in Article 2(1) of the Anti-Corruption Law. This ruling reclassified corruption from a formal offense to a material offense, thereby requiring proof of actual and quantifiable state financial loss. While this development enhances legal certainty and provides stronger protection against speculative or politically driven prosecutions, it simultaneously creates significant enforcement challenges. Establishing state financial loss necessitates protracted audit processes by institutions such as the Audit Board of Indonesia (BPK) or the Financial and Development Supervisory Agency (BPKP). Moreover, corruption produces diffuse, non-pecuniary harms—including diminished public trust, market distortions, and weakened democratic governance—that elude monetary quantification. Comparative analysis underscores divergent approaches. Civil law jurisdictions such as Germany and the Netherlands recognize the necessity of harm yet permit provisional measures prior to final quantification. Conversely, common law systems, including the United States and the United Kingdom, criminalize corrupt conduct irrespective of measurable loss, as exemplified by the FCPA and the Bribery Act 2010. International conventions (UNCAC, OECD Anti-Bribery Convention) similarly advocate flexible approaches that reconcile legal certainty with enforcement effectiveness. This research advances a two-tiered evidentiary framework: suspect designation should be permissible upon credible indications of corrupt conduct supported by provisional evidence of harm, with precise quantification deferred to trial. Such a model preserves the constitutional demand of legality while ensuring the practical efficacy of anti-corruption enforcement.